2005
DOI: 10.1007/s00418-005-0047-3
|View full text |Cite
|
Sign up to set email alerts
|

Specific localisation of gap junction protein connexin 32 in the gastric mucosa of horses

Abstract: In the glandular stomach, gap junctional intercellular communication (GJIC) plays an important role in the gastric mucosal defense system, and loss of GJIC is associated with ulcer formation. In spite of the high incidence of gastric ulcers in horses, particularly at pars nonglandularis, the presence of gap junctions in the equine stomach has not yet been studied. The objective was to obtain basic data on the distribution of gap junction protein connexin 32 (Cx32) in the different regions of normal equine gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Cx32 is mainly found along the membranes of foveolar cells and Cx26 is predominantly found within the cytoplasm of parietal cells [18][19][20]. In an investigation of Cx32 expression in gastritis, intestinal metaplasia and gastric carcinoma, Uchida et al [20] showed that Cx32 expression was significantly reduced in epithelial cells with gastritis and intestinal metaplasia compared to normal gastric mucosa, and was undetectable in carcinoma cells.…”
mentioning
confidence: 99%
“…Cx32 is mainly found along the membranes of foveolar cells and Cx26 is predominantly found within the cytoplasm of parietal cells [18][19][20]. In an investigation of Cx32 expression in gastritis, intestinal metaplasia and gastric carcinoma, Uchida et al [20] showed that Cx32 expression was significantly reduced in epithelial cells with gastritis and intestinal metaplasia compared to normal gastric mucosa, and was undetectable in carcinoma cells.…”
mentioning
confidence: 99%
“…It has been found that gap junctional intercellular communication (GJIC) plays an important role in the gastric mucosal defense system, and loss of GJIC is associated with ulcer formation. A recent study demonstrated the presence of specific gap junctions in the glandular mucosa of the equine stomach, however these gap junctions were absent in the squamous mucosa of the stomach [45]. This suggests that there are significant differences in the permeation pathway of the glandular vs. the squamous epithelium which may explain (in part) why in this study population, with a predominace of glandular ulcers, the sucrose blood test had a poorer diagnostic accuracy than expected.…”
Section: Discussionmentioning
confidence: 69%
“…Because of the important role of gap junctional intercellular communication (GJIC) in the equine gastric mucosal defense system, Fink et al (2006) have performed the missing immunohistochemical and in situ hybridization analysis of gap junction protein connexin 32 (Cx32) in this organ. Cx32 was found in the glandular regions, but was undetectable in squamous mucosa.…”
Section: Aspects Of Cell Membranes: Caveolins Transporters Junctionmentioning
confidence: 99%